Long-term surgical outcomes and prognostic factors of foveal detachment in pathologic myopia: based on the ATN classification - Jingyang Feng; Jiayi Yu; Qiuying Chen; Hao Zhou; Fenge Chen; Weijun Wang; Xun Xu; Ying Fan (BMC Ophthalmology, 2022)
Abstract Background To investigate the long-term surgical outcomes and prognostic factors of foveal detachment (FD) in pathological myopia. Methods This retrospective observational study included 59 patients with FD (61 eyes) who underwent pars plana vitrectomy at Shanghai General Hospital between June 2017 and July 2018 with follow-up for at least 24 months. Comprehensive ophthalmic examinations, including best-corrected visual acuity (BCVA) and swept-source optical coherence tomography, were assessed. Preoperative myopic maculopathy was evaluated according to the ATN classification. Results FD completely resolved in 59 of 61 eyes (96.7%). Mean duration of retinal reattachment was 12.10 ± 8.10 months. Mean logMAR BCVA improved from 1.34 ± 0.52 to 0.83 ± 0.43 at 24 months postoperatively (P < 0.001). Secondary macular hole occurred in 8 eyes (13.1%) with a mean period of 3.4 ± 4.1 weeks after primary surgery. In regression analyses, baseline myopic atrophy maculopathy (MAM) (B = 0.213, P = 0.005) and vitreomacular traction (VMT) (B = 0.292, P = 0.007) were adverse prognostic factors for postoperative BCVA. A more severe MAM revealed a delay in retinal reattachment (B = 5.670, P = 0.002). FD eyes with VMT (OR = 1.309, P = 0.003) or outer lamellar macular hole (O-LMH) (OR = 1.369, P < 0.001) were risk factors for postoperative secondary macular hole. Conclusions Vitrectomy was effective in the long-term for treating FD. Careful consideration is needed for those with VMT or O-LMH due to the high risk of secondary macular hole after vitrectomy. FD eyes with more severe MAM tended to have poorer postoperative BCVA and extended periods of retinal reattachment.